Cultural Treasures or Cash Cows?: Cheating Posterity and Selling Art Collections to Balance the Budget. Issue 1 (March 2015) - White, Pamela J.; Wasmund, Sadie
Throughout history, the value of art collections has often been too great an enticement to avoid their commodification. Nonetheless, museum advocates must fight to retain their collections even amidst pressure from forces that hold financial control and ultimate decision-making power over them. A case could be made that some view collections as cultural treasures while others view them as cash cows. For instance, the city of Detroit's bankruptcy, due to the national economic downturn and the decline of the city's economic strength, has fostered discussions of selling the Detroit Institute of Arts' collection. That city's financial—and cultural—crisis parallels situations faced by some museums that are nested in colleges and universities. The sagas of four museums nested in institutions of higher education are explored and compared: The Maier Museum at Randolph College; The Rose Museum at Brandeis University; Fisk University; and The University of Iowa. In a final analysis of these case studies and broader concerns, the authors advocate for nested museums to take a strong stance of financial self-sufficiency by creating cooperative ownership networks with other museums. Such a model aims to keep art collections safe from sale by continually keeping them on display at different museum locations while protecting their status as works kept for the public in perpetuity.